International law in antiquity - Bederman, David J (Cambridge University, 2013)
This study of the origins of international law contains up-to-date literature and archaeological evidence. David J. Bederman examines three critical areas in which law influenced ancient state relations - diplomacy, treaty-making and warfare - in the Near East (2800-700 BCE), the Greek city-states (500-338 BCE), and Rome (358-168 BCE).